PEMETAAN POTENSI UMKM DAN KETERSEDIAAN SARANA PRASARANA SERTA INFRASTUKTUR NAGARI PIANGGU, KECAMATAN lX LASI SUNGAI LASI, KABUPATEN SOLOK - Maisyarah; Wilis, Ratna; Nadela Putri, Fitria; Ikhwan, M; Yani Lubis, Sri; Denilson Asmi, Agus; Khaira, Kuntum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Micro, Small, and Medium Enterprises (UMKM)sector has become a pillar of the nagari's economy due to the shift in rural development paradigms from a centralistic approach to the one centered on local potential. However, the develoment of MSMEs in Nagari Pianggu, lX Koto Suangai Lasi District, is often hindered by the failure to integrate economic potential ponits with supervisory infrastructure and the accuracy of data visualization in development planning. The objective of this research is to creae basic spatial data on potential of MSMEs in nagari pianggu and to assess the availability of infastructure and facilities. The method used is qualitative descriptive with spatial analysis thru ArcGIS 10.8 software. Primary data were collected thru field observations using the timemark application to mark the absolute locations (plotting) of business actors and infastructure, which were then analyzed using the overlay method with secondary data in form of landsat 8 OLI/TRIS satelite imagery. The mappinf results serve as an objective decisionamaking instrument for the Nagari Government to identify "blind spots" in regional development with high productivity but minimal infastructure support. So, this research contributes to the formulation of data-based development policies, while academically strengthening the integration of people's economy analysis with spatial analysis in the context of rural development in West Sumatra.